PENEGAKAN HUKUM TERHADAP PRINSIP PERSAMAAN KEDUDUKAN DI HADAPAN HUKUM (PERSPEKTIF HUKUM ISLAM) - Hamzah K; Rizka Amelia Armin; Amirullah Sirajuddin (MADDIKA : Journal of Islamic Family Law, 2020)
The research objective was to determine the principle of equality before the law, to see the principle of equality before the law in the perspective of Islamic law. This type of research is literature research, then this research uses a qualitative approach. The data technique in this research is to collect written works in the form of books and so on, then read and record the materials needed to obtain information related to the discussion. The data management steps taken were analysis and descriptive. The results of the research show that equality before the law or as equality before the law is a very important principle in law enforcement. Equality before the law is a means that must be lived and implemented to decide problems, especially in criminal law, so that discrimination does not occur. At the time of the Prophet Muhammad saw that equality before the law in Islam was applied by the existence of the Madina Charter, one of the principles in which a person must act fairly without differentiating between ordinary people and elite society